FREQUENCY OF FAB SUBTYPES IN ACUTE MYELOID LEUKEMIA PATIENTS AT AGA KHAN UNIVERSITY HOSPITAL KARACHI - Harani, Mahadev S.; Adil, Salman Naseem; Shaikh, Mohammad Usman; Kakepoto, Ghulam Nabi; Khurshid, Mohammmad (Journal of Ayub Medical College Abbottabad, 2005)
Background: Acute myeloid leukemia (AML) is a heterogeneous disease. Therefore, various parameters are needed to classify this disease into subtypes, so that specific treatment approaches can be utilized effectively. The commonly used method for diagnosis and classification is based on FAB criteria using morphology and cytochemical stains. For some of the categories, immunophenotyping is necessary. The aim of present study is to determine the frequency of various sub types in acute myeloid leukemia using FAB criteria in our population. This will aid in the correct diagnosis of acute leukemia and hence proper management of the patients. Materials and Methods: This is descriptive case control study conducted at Aga Khan University Hospital from January 1999 to December 2000. The total number of subjects was 116 that included both adults and children. The patients were diagnosed on the basis of bone marrow morphology using FAB classification. Cytochemistry was done in all cases, while immunophenotyping was considered only in those cases that were found to be problematic. Results: Among 116 patients, 70 were males and 46 were females with male to female ratio 1.5:1. The age ranged between 6 months to 85 years with a mean age of 32 years. AML-M4 was the predominant French-American-British (FAB) subtype (36.2%) followed by M2 (30.25%), M3 (10.4%), M1 (8.7%), M0 (7.7%), M5a (3.5%), M5b (2.5%) and M6 (0.8%). Conclusions: The most common FAB subtype observed in our study was Acute myelomonocytic leukemia (M4) which is in accordance with studies reported from Saudia Arabia and a previous study reported from our institution. However,other national and international studies have reported Myeloblastic Leukemia with maturation (M2) as the predominant subtype of AML. Keywords: French-American-British (FAB) classification, Acute myeloid Leukemia (AML), subtypes.